Personalizing the theme park: psychometric profiling and physiological monitoring - Rennick-Egglestone, Stefan; Whitbrook, Amanda; Leygue, Caroline; Greensmith, Julie; Walker, Brendan; Benford, Steve; Schnädelbach, Holger; Reeves, Stuart; Marshall, Joe; Kirk, David; Tennent, Paul; Irune, Ainoje; et al. (Springer, 2011)
Theme parks are important and complex forms of entertainment, with a broad user-base, and with a substantial economic impact. In this paper, we present a case study of an existing theme park, and use this to motivate two research challenges in relation to user-modeling and personalization in this environment: developing recommender systems to support theme park visits, and developing rides that are personalized to the users who take part in them. We then provide an analysis, drawn from a real-world study on an existing ride, which illustrates the efficacy of psychometric profiling and physiological monitoring in relation to these challenges. We conclude by discussing further research work that could be carried out within the theme park, but motivate this research by considering the broader contribution to user-modeling issues that it could make. As such, we present the theme park as a microcosm which is amenable to research, but which is relevant in a much broader setting.